Efeitos da adição de átomos de Mn na rede do GaN via métodos de estrutura eletrônica - Mazini, Melânia Cristina [UNESP]; Sambrano, Julio Ricardo [UNESP]; Cavalheiro, Alberto Adriano; Leite, Douglas Marcel Gonçalves [UNESP]; Silva, José Humberto Dias da [UNESP] (Sociedade Brasileira de Química, 2010)
A computational method to simulate the changes in the electronic structure of Ga1-xMn xN was performed in order to improve the understanding of the indirect contribution of Mn atoms. This periodic quantum-mechanical method is based on density functional theory at B3LYP level. The electronic structures are compared with experimental data of the absorption edge of the GaMnN. It was observed that the indirect influence of Mn through the structural parameters can account for the main part of the band gap variation for materials in the diluted regime (x<0.08), and is still significant for higher compositions (x~0.18).
Indirect effects of the Mn incorporation on the electronic structure of nanocrystalline GaN
Keywords: GaN; diluted magnetic semiconductor (DMS); DFT